Clinical presentation and treatment in kratom withdrawal: a narrative review of case studies - Baran, Wojciech; Bartkiewicz, Patrycja; Lachowska, Ewelina; Jędrasek, Tomasz; Korman, Adrian; Al-Batool, Wafa (Journal of Education, Health and Sport, 2026)
Background. Kratom (Mitragyna speciosa) use is increasing internationally and case reports describe a range of withdrawal syndromes. Clinical guidance for recognizing and managing kratom withdrawal is limited. This narrative review of case reports synthesizes clinical features, management strategies, and outcomes among published patient cases. Aim. To characterize the clinical features, management strategies, and outcomes reported in published cases of kratom withdrawal. Additionally, identify common patterns in presentation and treatment that may inform preliminary clinical guidance for recognition and management. Methods. Article databases were searched for case studies related to kratom withdrawal. After screening titles/abstracts and full texts, 12 reports describing 16 individual patients were included. Data was extracted and findings were narratively synthesized across demographics/use characteristics, clinical presentation, pharmacological management, and outcomes. Results. Reported reasons for kratom use included self-treatment of opioid use disorder, pain, and psychiatric symptoms. Presentation varied from mild autonomic and gastrointestinal symptoms to severe, atypical syndromes. Opioid-like features of mild severity relative to usual opioid use predominated. Pharmacological management most commonly involved buprenorphine/naloxone. Clonidine and benzodiazepines were common adjuncts. Conclusions. Case-level evidence and existing literature indicates that kratom withdrawal most often presents as an opioid-like syndrome and that buprenorphine, with symptom-driven, conservative induction, was the most consistently effective treatment in reported cases. Interpretation is limited by small numbers, heterogeneous and incomplete reporting (dose/formulation/duration). Prospective, standardized reporting of exposure and outcomes and kratom-specific validation of withdrawal assessment tools are needed to inform evidence-based management.